2009
DOI: 10.1590/s0102-71822009000300015
|View full text |Cite
|
Sign up to set email alerts
|

Vidas em risco: a identidade profissional dos bombeiros militares

Abstract: RESUMO:Este artigo discute a configuração da identidade profissional do Bombeiro Militar da região da grande Florianópolis, SC. Para contemplar tal objetivo geral, os objetivos específicos e o referencial teórico enfocaram: caracterização da profissão, identidade, trabalho, escolha profissional e qualidade de vida. Quanto ao método, a pesquisa definiu-se como exploratória e descritiva, delineada como um levantamento. Utilizou-se um questionário semi-aberto. analisaram-se os dados quantitativa e qualitativament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
19

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 3 publications
0
3
0
19
Order By: Relevance
“…It identified that 55% of the firefighters studied presented symptoms of stress and found the major stress factors to be labor relations, work overload, and the lack of professional qualification and psychological support. Similarly, it was observed in another study (Natividade, 2009) that the risks of the profession, the organizational structure (hierarchy, discipline, standards) and the high requirement 'not to make mistakes' impact with the emergence of stress conditions in the work of the firefighters. The firefighters demonstrated the desire to discuss events that occur in their work environment to reduce this emotional distress, indicating that these discussions could be conducted by a specialist, preferably a psychologist.…”
Section: Firefighters and Mental Health/illnessmentioning
confidence: 66%
“…It identified that 55% of the firefighters studied presented symptoms of stress and found the major stress factors to be labor relations, work overload, and the lack of professional qualification and psychological support. Similarly, it was observed in another study (Natividade, 2009) that the risks of the profession, the organizational structure (hierarchy, discipline, standards) and the high requirement 'not to make mistakes' impact with the emergence of stress conditions in the work of the firefighters. The firefighters demonstrated the desire to discuss events that occur in their work environment to reduce this emotional distress, indicating that these discussions could be conducted by a specialist, preferably a psychologist.…”
Section: Firefighters and Mental Health/illnessmentioning
confidence: 66%
“…Essa expressiva fala de Teseu remete a achados de estudos (Gonzales et al, 2006;Monteiro et al, 2007;Natividade, 2009) de como, apesar dos riscos a que ficam expostos e da forte carga emocional decorrente das situações vivenciadas, a profissão de bombeiro costuma ser experimentada como fator de significativa realização pessoal, ancorado em reconhecimento social e apoio por parte da família. O tema do reconhecimento reaparece na alusão de Ulisses à valorização por parte da Corporação, todavia em sua negativa.…”
Section: Retaguarda Institucional Ao Sujeito Que Salva: Nuances Do Reunclassified
“…Alguns fatores ligados à autonomia do jovem, que interferem na escolha vocacional/profissional, são seus próprios interesses pessoais, preferências, gostos por uma ou outra área do conhecimento ou profissão (Almeida & Pinho, 2008;Faria, 2013;Luna, 2012;Magalhães, Straliotto, Keller, & Gomes, 2001;Natividade & Brasil, 2006). Muitas vezes, o interesse por determinada profissão surge do envolvimento ou experimentação de atividades ligadas à área desejada (Louzada & Silva, 2008;Ribeiro, Leal, Diamantino, & Bianchi, 2011).…”
Section: Escolha Vocacional/profissional E a Entrada Na Universidadeunclassified